Karakteristik Teks Laporan Hasil Observasi Siswa Kelas VIII SMP Negeri 15 Padang - Alyaa Dhiya Ulhaq; Ayu Gustia Ningsih; Yulianti Rasyid; Dewi Syafrina (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe three things, namely the structure, content, and linguistic characteristics of observation report texts of class VIII students of SMP Negeri 15 Padang. The type of research used is qualitative research using descriptive methods. The data analyzed are observation report texts written by class VIII students of SMP Negeri 15 Padang totaling 33 texts. The instrument in this study was the researcher herself. Data collection techniques used fishing techniques and documentation techniques. The data validation technique used was triangulation (cross-check). Data analysis consists of, namely data reduction, data presentation, and data verification. Based on the results of the study, the following three things can be concluded. First, overall 24 texts have a complete structure and 9 texts do not have a complete structure. Second, the content of the observation report texts of class VIII students of SMP Negeri 15 Padang shows that of the 33 texts analyzed, 24 observation report texts have complete content. Third, the linguistic characteristics found in the observation report texts of class VIII students at SMP Negeri 15 Padang are 21 texts that have complete linguistic characteristics and 12 texts do not have complete linguistic characteristics. In general, students' ability to write observation report texts is classified as good, but still needs improvement, especially in the aspect of linguistic characteristics.